2020
DOI: 10.1002/jmv.26472
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of neopterin in COVID‐19 patients

Abstract: In Coronavirus disease‐2019 (COVID‐19) cases, hyper inflammation is associated with the severity of the disease. High levels of circulating cytokines were reported in severe COVID‐19 patients. Neopterin produced by macrophages on stimulation with interferon‐gamma, which is an important cytokine in the antiviral immune response, hence it can be used to predict the severity of disease in COVID‐19 cases. In this study, it was aimed to determine the prognostic value of the neopterin for the prediction of severe di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
2
27
0
4
Order By: Relevance
“…In that study, higher neopterin levels were associated with a longer fever period, as well as a severer course of disease. Moreover, a recent report on hospitalized COVID-19 patients showed that neopterin levels were significantly Means and standard deviations (SD) are shown KYN/TRP kynurenine to tryptophan ratio, IFN-y interferon-gamma higher in severe cases compared to mild cases [15]. Besides supporting these findings, our study adds the trajectory of neopterin levels with repeated measurements, where we found that most patients with mild symptoms returned to normal neopterin levels at the end of the study period.…”
Section: Discussionsupporting
confidence: 85%
“…In that study, higher neopterin levels were associated with a longer fever period, as well as a severer course of disease. Moreover, a recent report on hospitalized COVID-19 patients showed that neopterin levels were significantly Means and standard deviations (SD) are shown KYN/TRP kynurenine to tryptophan ratio, IFN-y interferon-gamma higher in severe cases compared to mild cases [15]. Besides supporting these findings, our study adds the trajectory of neopterin levels with repeated measurements, where we found that most patients with mild symptoms returned to normal neopterin levels at the end of the study period.…”
Section: Discussionsupporting
confidence: 85%
“… 57 Likewise, a similar report showed that patients with severe COVID-19 had higher levels compared with mild cases on hospital admission and a four-fold increase compared with healthy controls. 58 …”
Section: Neopterin In Covid-19 Patientsmentioning
confidence: 99%
“…Neopterin (D-erythro-1'2'3'-trihydroxypropylpterin) of other species are less able of doing so. In patients, increased neopterin concentrations were documented in body fluids like serum, urine and cerebrospinal fluid (CSF), e.g., during cytokine therapies but also in diseases that are associated with activation of the Th1-type immune system such as mycobacterial infections, autoimmune pathologies and various forms of cancer and with viral infections including HIV-1 and SARS-CoV-1 [3,10,11] and recently also with SARS-CoV-2 [4][5][6].…”
Section: Neopterinmentioning
confidence: 99%
“…Similar to HIV-1 infection, elevated neopterin concentrations in serum and CSF are common also in patients with SARS-CoV-2 infection, and are predictive for the course of the infection [4][5][6]. However, in SARS-CoV-2 infection, an unusual pattern of CSF inflammation is commonly present with increased soluble markers like neopterin and beta2-microglobulin while white cell response and other immunologic features typical of CNS viral infections are absent [5].…”
Section: Neopterinmentioning
confidence: 99%
See 1 more Smart Citation